Foreign direct investment legislation and economic growth in Western Balkan countries: a panel analysis - Ibraimi, Xhemazie; Ziberi, Besime Fekri; Ahmad, Nawaz; Vveinhardt, Jolita (Technological and Economic Development of Economy, 2025)
Foreign direct investment (FDI) legislation plays a crucial role in fetching foreign investments. The objective of this study is to measure the impact of FDI on the Western Balkans countries (WBCs) and interpret the FDI law in the said countries. A panel data was obtained from the World Bank Indicators in order to conduct an empirical investigation. The sample is spread over twenty-eight years from 1995 to 2022. For econometric analysis, the study uses pooled ordinary least square (OLS), fixed effect (FE), random effect (RE), and Hausman test. The study also uses the Breuch and Pagan Lagrangian Multiplier test for Random Effect, the test for parameter constancy, the modified Wald test for groupwise heteroskedasticity, the Wooldridge test for autocorrelation, the test for serial correlation in residuals, and a test for normality. After a detailed analysis, the study concludes that FDI has a positive impact on the economic growth of WBCs. The study suggests that enforcing the rule of law on FDI will reduce the corruption index and create a favourable environment for WBCs to attract foreign investment.First published online 17 March 2025